How Hypertension Guidelines Address Social Determinants of Health: A Systematic Scoping Review. Issue 12 (11th December 2021) - Razon, Na'amah; Hessler, Danielle; Bibbins-Domingo, Kirsten; Gottlieb, Laura
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Patient-level and community-level social and economic conditions impact hypertension risk and control. We examined adult hypertension management guidelines to explore whether and how existing guidelines refer to social care activities. Objective: The objective of this study was to explore how hypertension guidelines reference social care activities. Research Design: A systematic scoping review of clinical guidelines for adult hypertension management. We employed a PubMed search strategy to identify all hypertension guidelines published in the United States between 1977 and 2019. We reviewed all titles to identify the most updated versions focused on nonpregnant adults with hypertension. We extracted instances where guidelines referred to social determinants of health (SDH) or social care activities. The primary outcome was how guidelines covered social care activities, defined using a framework adapted from the National Academies of Sciences, Engineering, and Medicine (NASEM). Results: Search terms yielded 126 guidelines. Thirty-six guidelines met the inclusion criteria. Of those, 72% (26/36) recommended social care activities as part of hypertension management; 58% recommended clinicians change clinical practice based on social risk information. These recommendations often lacked specific guidance around how to directly address social risk factors or reduce the impact of these risks on hypertension management. When guidelines referred to specific social factors, patient financial security was the most common. Over time, hypertension guidelines have included more references to SDH. Conclusion: Information about SDH is included in many hypertension guidelines, but few guidelines provide clear guidance for clinicians or health systems on how to identify and address social risk factors in the context of care delivery.